Are young Canadians supportive of proposed nutrition policies and regulations? An overview of policy support and the impact of socio-demographic factors on public opinion - Bhawra, Jasmin (Can J Public Health, 2018)
OBJECTIVES: Many countries, including Canada, are considering nutrition policies that seek to improve dietary behaviour and related health outcomes. The current study examined support for policy measures among youth and young adults in Canada. METHODS: Participants aged 16–30 years were recruited for online surveys using in-person intercept sampling in five Canadian cities as part of the Canada Food Study conducted in October–December, 2016 (n = 2729). Items included support for 21 specific policies in seven key areas: menu labelling, food package symbols and warnings, school policies, taxation and subsidies, zoning restrictions, marketing bans, and food formulation. Linear regression models examined support by age, sex, city, race/ethnicity, parental status, body mass index (BMI), and health literacy. RESULTS: Very high levels of support were observed for menu labelling in restaurants and schools, as well as food package symbols and warnings. Taxation, zoning restrictions (e.g., fast food and convenience stores near schools), and bans on marketing to children received relatively lower levels of support. In general, policy support increased with age for all 21 policies (p < 0.01) and greater health literacy for 4 policies (p < 0.05). Males were less supportive than females for 5 policies (p < 0.01). There were significant differences in support for specific race/ethnicity groups for 4 policies (p < 0.05). Support for menu labelling policies increased with BMI (p < 0.05). CONCLUSION: Overall, youth and young adults in Canada reported high levels of support for menu labelling, food package symbols/warnings, and school policies. Levels of support were generally consistent across socio-demographic subgroups, with some exceptions.